2007
DOI: 10.1007/s11055-007-0036-1
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of interleukin-10 on the development of epileptiform activity evoked by transient episodes of hypoxia in rat hippocampal slices

Abstract: The aim of the present work was to study the effects of interleukin-10 at concentrations of 1 and 10 ng/ml on the development of epileptiform discharges evoked in pyramidal neurons in field CA3 in rat hippocampal slices by transient episodes of hypoxia. Three 3-min episodes of hypoxia led to decreases in the generation threshold for evoked trains of population spikes and an increase in the number of population spikes per train in pyramidal neurons of field CA1. Interleukin-10 at a concentration of 1 ng/ml comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Proinflammatory cytokines are known to play a critical role in the pathogenesis of TLE (Moore et al, 2001 ; Vezzani et al, 2002 ; Li et al, 2011 ). A number of animal studies and clinical observations suggest an anticonvulsant effect of IL-10 (Kurreeman et al, 2004 ; Levin and Godukhin, 2007 ; Ishizaki et al, 2009 ; Youn et al, 2012 ). A recent analysis indicated neuroprotective effects of IL-10 against the development of hypoxia-evoked epileptiform activity in rat hippocampal slices (Levin and Godukhin, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proinflammatory cytokines are known to play a critical role in the pathogenesis of TLE (Moore et al, 2001 ; Vezzani et al, 2002 ; Li et al, 2011 ). A number of animal studies and clinical observations suggest an anticonvulsant effect of IL-10 (Kurreeman et al, 2004 ; Levin and Godukhin, 2007 ; Ishizaki et al, 2009 ; Youn et al, 2012 ). A recent analysis indicated neuroprotective effects of IL-10 against the development of hypoxia-evoked epileptiform activity in rat hippocampal slices (Levin and Godukhin, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of animal studies and clinical observations suggest an anticonvulsant effect of IL-10 (Kurreeman et al, 2004 ; Levin and Godukhin, 2007 ; Ishizaki et al, 2009 ; Youn et al, 2012 ). A recent analysis indicated neuroprotective effects of IL-10 against the development of hypoxia-evoked epileptiform activity in rat hippocampal slices (Levin and Godukhin, 2007 ). In experimental hyperthermic seizures in rat models, the seizure threshold temperature in IL-10 treated rats was significantly upregulated compared to normal controls (Ishizaki et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Suppression of miR‐187 using an antagomir during the first hours after status epilepticus increased levels of IL‐10 in the early phases of epileptogenesis (Alsharafi et al, ). IL‐10 has an anti‐convulsant effect in models of hypoxic ischemic‐induced seizures and febrile seizures (Levin and Godukhin, ; Ishizaki et al, ), and is known to provide trophic support to neurons. While not tested in this study, antagonizing miR‐187 in the acute and latent phase after status epilepticus may provide neuroprotection through up‐regulation of IL‐10, and may thus be a desirable target to prevent spontaneous recurrent seizures after an epileptogenic insult.…”
Section: Micrornas Regulating Inflammation In Epilepsy and Epileptogementioning
confidence: 99%
“…Indeed, IL-10 deactivates macrophages, which in turn decreases the production of cytokines by T cells (Youn, 2013). Several animal studies and clinical observations suggest an anticonvulsant effect of IL-10; one report showed protective effects of IL-10 against the development of epileptiform activity evoked by transient episodes of hypoxia in rat hippocampal slices (Levin and Godukhin, 2007). Production of IL-10 in blood is controversial; some authors reported no differences in plasma IL-10 between patients with focal seizure and control (Virta et al, 2002), whereas IL-10 production was significantly lower in patients suffering from focal seizure than in healthy control (Li et al, 2011).…”
Section: Cytokines and Ros/rsn In Cultured Pbmcmentioning
confidence: 99%